2017
DOI: 10.1016/j.cub.2017.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Contextually Mediated Spontaneous Retrieval Is Specific to the Hippocampus

Abstract: SUMMARY Although it is now well established that the hippocampus supports memory encoding [1, 2], little is known about hippocampal activity during spontaneous memory retrieval. Recent intracranial electroencephalographic (iEEG) work has shown that hippocampal activity during encoding predicts subsequent temporal organization of memories [3], supporting a role in contextual binding. It is an open question, however, whether the hippocampus similarly supports contextually mediated processes during retrieval. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 44 publications
(62 reference statements)
5
38
0
Order By: Relevance
“…While gamma power increases co-occurred with alpha/beta power decreases in occipital/posterior regions [66], no such co-localization was evident in left lateralized areas involved in semantic processing. Consequently, if the analysis in our study was limited to increases in broad band gamma power changes, a common practice in iEEG analysis [21][22][23][24][25] [9,21,22] the prominent changes in alpha/beta power related to word processing would have been missed. Our findings are exemplary in demonstrating that limiting analysis to very narrow parts of the time-frequency spectrum restricts the potential insights that can be drawn from the data.…”
Section: Discussionmentioning
confidence: 99%
“…While gamma power increases co-occurred with alpha/beta power decreases in occipital/posterior regions [66], no such co-localization was evident in left lateralized areas involved in semantic processing. Consequently, if the analysis in our study was limited to increases in broad band gamma power changes, a common practice in iEEG analysis [21][22][23][24][25] [9,21,22] the prominent changes in alpha/beta power related to word processing would have been missed. Our findings are exemplary in demonstrating that limiting analysis to very narrow parts of the time-frequency spectrum restricts the potential insights that can be drawn from the data.…”
Section: Discussionmentioning
confidence: 99%
“…An across‐subject correlation showed that greater hippocampal activity during encoding predicted increased serial recall. In a followup study, Long et al () examined both hippocampal and neocortical HFA during the retrieval phase of the same free recall task. They divided recall events into three classes: recall of items from the immediately preceding list (correct recalls), recall of items from other study lists or items not studied (intrusions) and periods of searching with no recall event (deliberations).…”
Section: The Hippocampus and Serial‐order Memorymentioning
confidence: 99%
“…Second, we examined a memory retrieval contrast, wherein epochs of time leading up to verbalization of a recalled item are compared to matched epochs of time, from other word lists, where no recall occurs (e.g. 29,40,41; see Methods for details). We refer to these matched periods as "deliberation" intervals.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, we aimed to contrast activity related to successful retrieval against activity during which subjects were liable to try, but fail, to recall a word. This paradigm has been employed in several prior studies examining the neural correlates of free recall (3,29,41,40). However, free-recall tasks inherently confound neural process responsible for episodic retrieval with processes responsible for vocalization and motor preparatory behavior.…”
Section: Discussionmentioning
confidence: 99%